The Influence of Responsive Parenting and Balanced Nutrition on Early Childhood Independence and Stunting Prevention - Zahrotunnisa, Amalia; Hasibuan, Rachma; Fauziyah, Cicik; Siti Jenar, Mauly; Aminatul Sholikah, Alfina; Krit, Ponghi; Sok, Vann (Journal of Islamic Education Students (JIES), 2025)
Responsive parenting and balanced nutrition are essential factors supporting the holistic development of early childhood. This study examines the influence of these two factors on children’s independence and stunting prevention using a quantitative correlational approach involving 46 parents at KB RA Mina Jadid, Mojokerto. Data were collected through a Likert-scale questionnaire and analyzed using descriptive statistics and Pearson Product Moment correlation. The results show that responsive parenting (4.46), balanced nutrition (4.33), and children’s independence (4.25) fall into the high category. Strong positive correlations were found between responsive parenting and independence (r = 0.71), balanced nutrition and independence (r = 0.76), as well as between parenting and nutrition (r = 0.77). Anthropometric measurements also indicate that most children fall within the normal growth range. These findings confirm that responsive parenting and balanced nutrition significantly contribute to enhancing children’s independence and reducing the risk of stunting.